2018
DOI: 10.1002/ldr.2944
|View full text |Cite
|
Sign up to set email alerts
|

Urban soils as hot spots of anthropogenic carbon accumulation: Review of stocks, mechanisms and driving factors

Abstract: Urban soils and cultural layers may accumulate C over centuries and consequently large C stocks may be sequestered beneath cities. Processes and mechanisms leading to high C accumulation in urban soils remain unknown. Data on soil organic carbon (SOC), soil inorganic carbon (SIC), black (pyrogenic) carbon (BC), and nitrogen contents and stocks in urban soils were collected from 100 peer‐reviewed papers. The database (770 data points for SOC, SIC, and BC stocks from 116 cities worldwide) was analysed considerin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
68
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 117 publications
(79 citation statements)
references
References 95 publications
8
68
3
Order By: Relevance
“…pollution) and provide further benefits to surrounding landscapes. Each broad landscape type (agricultural, urban and natural areas) demands a different suites of ES, which should be the target of management to enhance ES provision by road verges of the greatest stocks of black carbon (produced from burning fossil fuels; reviewed in Vasenev & Kuzyakov, 2018…”
Section: Carbon Sequestration and Storagementioning
confidence: 99%
See 1 more Smart Citation
“…pollution) and provide further benefits to surrounding landscapes. Each broad landscape type (agricultural, urban and natural areas) demands a different suites of ES, which should be the target of management to enhance ES provision by road verges of the greatest stocks of black carbon (produced from burning fossil fuels; reviewed in Vasenev & Kuzyakov, 2018…”
Section: Carbon Sequestration and Storagementioning
confidence: 99%
“…Maps and data were produced by drawing polygons around road verges using satellite imagery from Google Earth and verifying using Google Street View (Google, 2019), then importing to ArcMap 10.5.1 (ESRI, 2017). Road verge widths were calculated by creating centrelines for each road verge, converting them to points at 5 m intervals, measuring the distance from each point to the nearest road verge edge, then multiplying by 2 average value for grasslands (0.054 kg C m −2 year −1 ; reviewed in Conant, Paustian, & Elliott, 2001), which is probably a conservative estimate (Bouchard et al, 2013;Vasenev & Kuzyakov, 2018), then they may sequester 0.015 Gt C/year globally-nearly 1% of the annual carbon sink provided by the world's 4 million km 2 of forests (Pan et al, 2011).…”
Section: G Lobal E X Tent Of Road Verg E Smentioning
confidence: 99%
“…In this study, we found that there was no significant difference in the ratios of LOC to TOC caused by the conversion of agricultural land use scenarios, although significantly different contents of TOC and LOC among different agricultural land use scenarios were observed, suggesting that the ratio of LOC to TOC may not be the optimal indicator for assessing the stability and and much more chemical fertilizers were then needed to reinforce the supply of available nutrients for crops, which may further aggravate soil quality degradation and have negative impacts on the sustainability of agricultural land. In addition, the notable changes of subsoil organic carbon and its labile fractions suggest that more attention should be paid to the changes in subsoil carbon caused by agricultural land use changes in urban agricultural areas because agricultural land use is easily affected by rapid urbanization and substantial amounts of SOC are sequestered in the subsoil of suburbs (Vasenev & Kuzyakov, 2018).…”
Section: Effects Of Agricultural Land Use Change On Soc Stability Amentioning
confidence: 99%
“…With rapid population growth and economic development, greater demands for agricultural products (i.e., food and bioenergy) have resulted in the expansion of agricultural land areas and enhancement of the degree of agricultural intensification (Alexander et al, 2015;Chou, Dong, Wang, & Fu, 2015;Lai et al, 2016;Piquer-Rodríguez et al, 2018;Vasenev & Kuzyakov, 2018). Compared with agricultural expansion, agricultural intensification plays a major role in meeting the growing demands for agricultural products (Johnson, Runge, Senauer, Foley, & Polasky, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation